A wear-resistant liquid-cooled cable with ultra-large current load for new energy
By adopting a combined structure of composite polyvinyl chloride insulating layer, copper tape shielding layer, aluminum alloy heat transfer layer and composite cable material outer sheath layer in liquid-cooled cable, the liquid-cooled cable resistance in applications with excessive current load is solved. The problem of insufficient wearability and high-temperature heat dissipation efficiency has achieved higher wear resistance and heat dissipation performance.
Patent Information
- Application Number
- CN202411014615.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-26
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-07-26
AI Technical Summary
Existing liquid-cooled cables have problems with wear resistance and insufficient heat dissipation efficiency in high-temperature environments in applications with excessive current loads.
A liquid-cooled cable structure consisting of a conductor, an insulating layer, a shielding layer, a heat exchange layer and an outer sheath layer, wherein the insulating layer is made of composite polyvinyl chloride, the shielding layer is covered with copper strip, and the heat exchange layer is made of aluminum alloy The heat conducting pipe is wound, and the outer sheath layer is made of composite cable material, including thermal conducting filler and thermal insulation filler.
It significantly improves the wear resistance of the cable and the heat dissipation efficiency in high-temperature environments, extends the service life of the cable, and ensures the stable operation and safety of the cable under high-temperature environments.
Smart Images

Figure CN118782313B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of liquid cooling cable processing, and in particular to a wear-resistant liquid cooling cable with an ultra-large current load for new energy. Background Art
[0002] In modern society, with the continuous growth of energy demand and the rapid development of new energy technologies, traditional cables can no longer fully meet the needs of efficient energy transmission. Especially in application scenarios with ultra-large current loads, such as electric vehicle charging systems, large-scale renewable energy power stations, and high-performance computing equipment, cables are required to have high conductivity, wear resistance, and excellent heat dissipation performance. Therefore, it is particularly important to develop a wear-resistant liquid-cooled cable that can meet these requirements.
[0003] In the existing technology, the improvement of the performance of liquid-cooled cables mostly stays on the optimization of the internal structure of the liquid-cooled cables, while ignoring that the cable material itself can bring significant improvement to the performance of the liquid-cooled cables, such as:
[0004] Patent application CN2019106097592 discloses a liquid-cooled cable, which has a plurality of water grooves evenly arranged axially on the inner wall of the cable sheath, and a plurality of water grooves evenly arranged axially on the inner wall of the cable inner sheath. The cable outer sheath layer used is any one of TPU sheath, TPE sheath, and TPR sheath. The outer sheath material used in the liquid-cooled cable is not wear-resistant and has no heat insulation properties. The heat dissipation performance will be significantly reduced at high temperatures, and the material used for the inner sheath is not clearly defined, and it cannot be guaranteed that the conductor and the coolant can perform efficient heat exchange.
[0005] Patent application CN2022101966907 discloses a liquid-cooled cable. The main method for improving the heat exchange between the coolant and the conductor is to coat the outer wall of the insulation layer with thermal conductive aluminum foil. This method improves the thermal conductivity of the insulation layer by wrapping it with aluminum foil. Although this method can improve the thermal conductivity efficiency to a certain extent, the simple coating method cannot guarantee the service life of the aluminum foil layer. During the movement or bending of the cable, the aluminum foil is very easy to break and fall off, resulting in uneven heat dissipation inside the cable, causing accelerated aging and damage of the material.
[0006] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0007] The purpose of the present invention is to provide a wear-resistant liquid-cooled cable with ultra-large current load for new energy, which is used to solve the technical problem in the prior art that the wear resistance of liquid-cooled cables and the heat dissipation efficiency in high temperature environments need to be further improved.
[0008] The purpose of the present invention can be achieved through the following technical solutions:
[0009] A wear-resistant liquid-cooled cable with an ultra-large current load for new energy use, comprising a plurality of conductors, the exteriors of which are sequentially provided with an insulating layer, a shielding layer and an outer sheath layer; a heat exchange layer composed of a plurality of heat exchange tubes is provided between the shielding layer and the outer sheath layer, and the plurality of heat exchange tubes are all provided in a spiral shape;
[0010] The insulating layer is obtained by extruding composite polyvinyl chloride and coating it on the outside of the conductor;
[0011] The shielding layer is obtained by wrapping the copper tape over the insulation layer;
[0012] The heat exchange layer is obtained by winding a plurality of heat conducting pipes for conveying cooling liquid around the outside of the shielding layer, wherein the cooling pipes are made of aluminum alloy;
[0013] The outer sheath layer is obtained by extruding the composite cable material and coating it on the outside of the heat exchange layer;
[0014] The composite cable material comprises the following components in parts by weight: 100 parts of composite polyolefin and 20-30 parts of auxiliary materials, wherein the composite polyolefin is composed of a mixture of a polymer matrix and a heat-insulating filler.
[0015] Furthermore, the composite polyvinyl chloride includes the following components in parts by weight: 100 parts of polyvinyl chloride, 20-50 parts of thermal conductive fillers, 30-50 parts of plasticizers, 2-5 parts of stabilizers, 0.5-2 parts of lubricants, 0.5-1 parts of antioxidants and 0.5-1 parts of ultraviolet stabilizers, the plasticizer is a diester of phthalic acid, the stabilizer is one or more of a diester zinc stabilizer, a calcium zinc heat stabilizer HX-10 and a lead-free calcium zinc stabilizer LX-800, the lubricant is one or more of magnesium stearate, calcium stearate, zinc stearate and polyethylene wax, the antioxidant is one or more of 2,6-di-tert-butylparacresol, triphosphate and di-tert-butylparaphenol, and the ultraviolet stabilizer is one or more of UV-326, UV-327 and HALS.
[0016] Furthermore, the preparation method of the thermal conductive filler comprises the following steps:
[0017] A1. Add alumina particles and aluminum nitride particles into a calcining furnace, raise the furnace temperature to 400-600°C, introduce hexafluoropropylene gas at a rate of 0.1-0.5 L / min, and keep the temperature for 2-4 hours to obtain a fluorinated filler matrix;
[0018] A2, adding the fluorinated filler matrix, 0.5-2wt% 3-aminopropyltriethoxysilane solution and anhydrous ethanol into a reaction kettle, raising the temperature of the reaction kettle to 80-120° C., keeping the temperature for 1-3 hours, and post-treating to obtain a thermally conductive filler matrix;
[0019] A3. Weigh 60 parts of thermal conductive filler matrix, 2-5 parts of silver nanowires and 5-10 parts of single-walled carbon nanotubes by weight and mix them evenly to obtain a thermal conductive filler.
[0020] Furthermore, in step A1, the mass ratio of aluminum oxide particles to aluminum nitride particles is 1-2g:2-4g; in step A2, the amount ratio of the fluorinated filler matrix, 0.5-2wt% 3-aminopropyltriethoxysilane solution and anhydrous ethanol is 8-10g:2-3g:40-50mL, and the post-treatment includes: after the reaction is completed, filtering, placing the filter cake in a drying oven at a temperature of 80°C and drying it until the filter cake is constant weight, to obtain a thermally conductive filler matrix.
[0021] Furthermore, the preparation method of the thermal insulation filler comprises the following steps:
[0022] B1, adding magnesium oxide particles, magnesium carbonate particles and hydrogen peroxide solution into a reactor, reacting at room temperature for 1-2 hours, and post-processing to obtain an activated filler matrix;
[0023] B2, adding the activated filler matrix and 0.5-2wt% 3-aminopropyltriethoxysilane solution into a reaction kettle, raising the temperature of the reaction kettle to 40-60° C., keeping warm and stirring for 1-2 hours, and post-treating to obtain a silanized filler matrix;
[0024] B3. Place the silanized filler matrix in a pressure chamber of 10 -2 -10 -3 Into a 1000-20000 ton ammonia nitriding furnace, high-purity ammonia is introduced, the gas pressure is maintained at 0.1-1 Torr, the temperature is raised to 500-800°C, the temperature is kept for 2-3 hours, and the sample chamber is gradually cooled to room temperature to obtain a modified filler matrix;
[0025] B4. Weigh 30 parts of aluminum hydroxide particles, 30-50 parts of modified filler matrix, 5-10 parts of talc powder, 5-10 parts of silicon powder and 5-20 parts of hollow glass beads by weight and mix them evenly to obtain an insulating filler.
[0026] Furthermore, in step B1, the amount ratio of magnesium oxide particles, magnesium carbonate particles and hydrogen peroxide solution is 3-5g:2-3g:5-8mL, and the post-treatment includes: after the reaction is completed, suction filtration, placing the filter cake in a reactor at a temperature of 80°C and drying it until the filter cake has a constant weight, thereby obtaining an activated filler matrix; in step B2, the amount ratio of the activated filler matrix and 0.5-2wt% 3-aminopropyltriethoxysilane solution is 1-2g:4-5mL, the stirring rate is 120-180rpm, and the post-treatment includes: after the reaction is completed, suction filtration, placing the filter cake in a reactor at a temperature of 80°C and drying it until the filter cake has a constant weight, thereby obtaining a silanized filler matrix.
[0027] Furthermore, the preparation method of the composite polyolefin comprises the following steps:
[0028] C1. Add benzoyl peroxide, toluene and dimethyl sulfoxide into a reaction kettle and stir at room temperature for 15-20 minutes to obtain an initiator solution;
[0029] C2, adding the initiator solution, phenyl methacrylate, acrylonitrile and 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane into the reaction kettle, raising the temperature of the reaction kettle to 60-80° C., and stirring for 2-4 hours to obtain a polymer matrix solution;
[0030] Reaction equation:
[0031]
[0032] Reaction principle: Benzoyl peroxide acts as a free radical initiator to initiate the disconnection of the double bonds of phenyl methacrylate, acrylonitrile and 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane, and a free radical addition reaction occurs to obtain a polymer.
[0033] C3. Add the polymer matrix solution, thermal insulation filler and deionized water into the reactor, increase the temperature of the reactor to 70-80°C, keep the temperature for 1-2 hours, and perform post-treatment to obtain the composite polyolefin.
[0034] Furthermore, in step C1, the amount ratio of benzoyl peroxide, toluene and dimethyl sulfoxide is 0.8-1g:12-15mL:12-15mL, and the stirring rate is 120-150rpm; in step C2, the amount ratio of initiator solution, phenyl methacrylate, acrylonitrile and 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane is 25-30mL:3-5g:3-4g:3-4g, and the stirring rate is 120-180rpm; in step C3, the amount ratio of polymer matrix solution and insulating filler is 80-100mL:20-25g, and the post-treatment operation is: placing the reaction solution on a rotary evaporator, setting the pressure to 2-5kPa, and removing the solvent by low-pressure evaporation until the precipitate is constant weight, placing the precipitate in a drying oven at a temperature of 80°C until the precipitate is constant weight, and obtaining a composite polyolefin.
[0035] Furthermore, the extrusion coating of the insulating layer includes the following steps: adding the composite polyvinyl chloride into a twin-screw extruder, the temperatures of the seven temperature zones of the twin-screw extruder from the feed port toward the discharge port are 160°C, 165°C, 165°C, 170°C, 170°C, 180°C, and 180°C respectively, the main engine speed of the twin-screw extruder is 80-120rpm, and the pressure is 100-150bar, and after melt extrusion, it is coated on the outside of the conductor to obtain an insulating layer.
[0036] Furthermore, the extrusion coating of the outer sheath layer includes the following steps: adding the composite cable material into a twin-screw extruder, the temperatures of the seven temperature sections of the twin-screw extruder from the feed port to the discharge port are 160°C, 165°C, 165°C, 170°C, 170°C, 180°C, and 180°C respectively, the main engine speed of the twin-screw extruder is 80-120rpm, and the pressure is 100-150bar. After melt extrusion, it is coated on the outside of the shielding layer to obtain a cable precursor, and the cable precursor is transferred to a box filled with water vapor, heat-insulated for 6-8h, cooled and discharged to obtain a cable.
[0037] Furthermore, the auxiliary materials of the composite cable material include the following components in parts by weight: 30-50 parts of plasticizer, 2-5 parts of stabilizer, 0.5-2 parts of lubricant, 0.5-1 parts of antioxidant and 0.5-1 parts of UV stabilizer, the plasticizer is a diester of phthalic acid, the stabilizer is one or more of a diester zinc stabilizer, a calcium zinc heat stabilizer HX-10 and a lead-free calcium zinc stabilizer LX-800, the lubricant is one or more of hard magnesium stearate, calcium stearate, zinc stearate and polyethylene wax, the antioxidant is tert-butyl hydroxybenzoate, and the UV stabilizer is UV-531. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0039] Figure 1 It is a schematic diagram of the cross-sectional structure of the military cable in the present invention;
[0040] In the figure: 100, outer sheath layer; 200, heat exchange layer; 300, shielding layer; 400, insulation layer; 500, conductor.
[0041] The present invention has the following beneficial effects:
[0042] 1. The wear-resistant liquid-cooled cable with ultra-large current load for new energy of the present invention has an outer sheath layer made of wear-resistant and heat-insulating materials. The wear-resistant materials enable the outer sheath layer to resist mechanical damage and abrasion in the external environment, thereby extending the service life of the cable. At the same time, the heat-insulating property enables the outer sheath layer to effectively isolate external heat sources, thereby preventing the external high temperature from adversely affecting the internal structure and performance of the cable. An insulating layer made of high-efficiency heat-conducting materials is arranged inside the cable to enhance the thermal conductivity of the cable, thereby ensuring the stable operation and safety of the cable under large current loads, and effectively preventing overheating, thereby improving the overall thermal management capability of the cable, so that the cable can still maintain excellent electrical performance in a high temperature environment. The cooperation of various layers of the cable not only improves the overall thermal management and mechanical properties of the cable, but also ensures that the cable can operate stably for a long time in harsh use environments.
[0043] 2. In the preparation process of the wear-resistant liquid-cooled cable with ultra-large current load for new energy use of the present invention, a mixture of aluminum nitride particles and aluminum oxide particles is used to prepare a high-efficiency thermal conductive filler through fluorination and surface silanization treatment. In the fluorination process, hexafluoropropylene is used to modify the surface of the aluminum nitride particles and the aluminum oxide particles at high temperature to form fluorine groups on their surface, thereby further improving the insulation and dielectric constant of the insulating layer; in the silanization process, 3-aminopropyltriethoxysilane is used to modify the surface of the fluorinated particles to generate a layer of silane molecules on its surface. At high temperature, the silane molecules react to form chemical bonds that can be tightly combined with inorganic materials. Through these processing steps, the obtained insulating layer not only has excellent thermal conductivity, but also can effectively improve the service life and stability of the cable under ultra-large current load.
[0044] 3. In the preparation process of the wear-resistant liquid-cooled cable with ultra-large current load for new energy use of the present invention, a polymer matrix is prepared by cross-linking polymerization of phenyl methacrylate, acrylonitrile and 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane, wherein 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane is used as a cross-linking agent for the reaction. 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane not only provides functional groups for the polymerization of phenyl methacrylate and acrylonitrile, but also the remaining alkoxy groups after the reaction are hydrolyzed to generate active groups that are tightly combined with the thermal insulation filler to make the structure of the outer sheath layer more compact, thereby effectively improving the structural density of the outer sheath. Thereby, the overall mechanical properties and durability of the cable are improved; the epoxy group in phenyl methacrylate also provides an active group for the polymer matrix, making the polymer matrix and the inorganic material more closely combined; the nitrogen group in acrylonitrile cooperates with the low-pressure aminated magnesium oxide particles and magnesium carbonate particles to improve the flame retardancy of the cable; at the same time, in the process of preparing the thermal insulation filler, the nitridation treatment also improves the thermal insulation capacity of the thermal insulation filler, so that the outer sheath layer can be more effectively isolated from the external heat source, protecting the internal structure of the cable from the influence of high temperature, and cooperating with acrylonitrile to improve the high temperature resistance and flame retardancy of the cable. Through these processing steps, the obtained outer sheath layer not only has excellent thermal insulation performance, but also can effectively improve the mechanical properties of the outer sheath layer. DETAILED DESCRIPTION
[0045] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] Example 1
[0047] S1. Preparation of composite polyvinyl chloride
[0048] Alumina particles and aluminum nitride particles were added into a calcining furnace at a mass ratio of 1:4, the furnace temperature was raised to 400°C, hexafluoropropylene gas was introduced at a rate of 0.1 L / min, and the reaction was carried out for 2 hours to obtain a fluorinated filler matrix;
[0049] A fluorinated filler matrix, a 0.5 wt% 3-aminopropyltriethoxysilane solution and anhydrous ethanol were added to a reactor in a dosage ratio of 8 g:2 g:40 mL, the temperature of the reactor was raised to 80° C., and the reaction was kept warm for 1 hour. After the reaction was completed, the filter was filtered and the filter cake was placed in a drying oven at a temperature of 80° C. and dried until the filter cake had a constant weight, thereby obtaining a thermally conductive filler matrix;
[0050] Weigh 60 parts by weight of a thermally conductive filler matrix, 2 parts of silver nanowires, and 5 parts of single-walled carbon nanotubes and mix them evenly to obtain a thermally conductive filler;
[0051] 100 parts of polyvinyl chloride, 20 parts of thermal conductive filler, 30 parts of phthalic acid diester, 2 parts of diester zinc stabilizer, 0.5 parts of polyethylene wax, 0.5 parts of 2,6-di-tert-butyl-p-cresol and 0.5 parts of UV-326 were weighed by weight and mixed evenly to obtain composite polyvinyl chloride.
[0052] S2. Preparation of thermal insulation filler
[0053] Add magnesium oxide particles, magnesium carbonate particles and hydrogen peroxide solution into a reactor in a dosage ratio of 3g:2g:5mL, react at room temperature for 1h, and after the reaction is completed, filter and place the filter cake in a reactor at a temperature of 80°C to dry until the filter cake has a constant weight, thereby obtaining an activated filler matrix;
[0054] The activated filler matrix and 0.5wt% 3-aminopropyltriethoxysilane solution were added to the reactor at a dosage ratio of 1g:4mL, the temperature of the reactor was raised to 40°C, and the mixture was stirred for 1h at a stirring rate of 120rpm. After the reaction was completed, the filter cake was filtered and placed in a reactor at a temperature of 80°C to dry until the filter cake had a constant weight, thereby obtaining a silanized filler matrix;
[0055] The silanized filler matrix is placed in a pressure of 10 -2 Into a 1000-ton ammonia nitriding furnace, high-purity ammonia is introduced, the gas pressure is maintained at 0.1 Torr, the temperature is raised to 500°C, the temperature is kept for 2 hours, and the sample chamber is gradually cooled to room temperature to obtain a modified filler matrix;
[0056] 30 parts of aluminum hydroxide particles, 30 parts of modified filler matrix, 5 parts of talcum powder, 5 parts of silicon powder and 5 parts of hollow glass beads were weighed and mixed evenly to obtain a thermal insulation filler.
[0057] S3. Preparation of polymer matrix
[0058] Benzoyl peroxide, toluene and dimethyl sulfoxide were added into the reaction kettle at a ratio of 0.8 g:12 mL:12 mL, and stirred at room temperature for 15 min at a stirring rate of 120 rpm to obtain an initiator solution;
[0059] The initiator solution, phenyl methacrylate, acrylonitrile and 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane were added into the reaction kettle at a ratio of 25 mL: 3 g: 3 g: 3 g, the temperature of the reaction kettle was raised to 60° C., and the mixture was stirred for 2 h at a stirring rate of 120 rpm to obtain a polymer matrix solution;
[0060] The polymer matrix solution, the insulating filler and the deionized water were added into the reactor in the amount ratio of 80mL:20g:15mL, the temperature of the reactor was raised to 70°C, and the reaction was kept warm for 1h. The reaction liquid was placed on a rotary evaporator with the pressure set to 2-5kPa, and the solvent was removed by low-pressure evaporation until the precipitate reached a constant weight. The precipitate was placed in a drying oven at a temperature of 80°C until the precipitate reached a constant weight to obtain a composite polyolefin.
[0061] Weigh 30 parts of phthalic acid diester, 2 parts of calcium zinc heat stabilizer HX-10, 0.5 parts of calcium stearate, 0.5 parts of tert-butyl hydroxybenzoate and 0.5 parts of UV-531 by weight, and mix them evenly to obtain an auxiliary material;
[0062] 100 parts of composite polyolefin and 20 parts of auxiliary materials are weighed and mixed evenly to obtain a composite cable material.
[0063] S4. Assemble the cables
[0064] A plurality of conductors 500 are arranged in parallel along their length direction to obtain a conductive core, wherein the conductor 500 is a copper core conductor with a surface coated with an insulating rubber layer;
[0065] The composite polyvinyl chloride is added into a twin-screw extruder, and the temperatures of the seven temperature sections of the twin-screw extruder from the feed port to the discharge port are 160°C, 165°C, 165°C, 170°C, 170°C, 180°C, and 180°C, respectively. The main engine speed of the twin-screw extruder is 80rpm, and the pressure is 100bar. After melt extrusion, the composite polyvinyl chloride is coated on the outside of the conductor 500 to obtain the insulating layer 200;
[0066] The shielding layer 300 is obtained by wrapping the insulating layer 200 with a copper tape;
[0067] The heat exchange layer 200 is obtained by winding a plurality of heat conducting pipes for conveying cooling liquid around the outside of the shielding layer, wherein the cooling pipes are made of aluminum alloy;
[0068] The composite cable material is added into a twin-screw extruder. The temperatures of the seven temperature zones of the twin-screw extruder from the feed port to the discharge port are 160°C, 165°C, 165°C, 170°C, 170°C, 180°C, and 180°C, respectively. The main engine speed of the twin-screw extruder is 80rpm, and the pressure is 100bar. After melt extrusion, it is coated on the outside of the heat exchange layer 200 to obtain a cable precursor. The cable precursor is transferred to a box filled with water vapor, kept warm for 6 hours, cooled and discharged to obtain a cable.
[0069] Example 2
[0070] S1. Preparation of composite polyvinyl chloride
[0071] Alumina particles and aluminum nitride particles were added into a calcining furnace at a mass ratio of 1:2, the furnace temperature was raised to 500°C, hexafluoropropylene gas was introduced at a rate of 0.5 L / min, and the reaction was carried out for 3 hours to obtain a fluorinated filler matrix;
[0072] A fluorinated filler matrix, a 2wt% 3-aminopropyltriethoxysilane solution and anhydrous ethanol were added into a reactor in a dosage ratio of 8g:3g:50mL, the temperature of the reactor was raised to 100°C, and the reaction was kept warm for 2h. After the reaction was completed, the filter was filtered and the filter cake was placed in a drying oven at a temperature of 80°C and dried until the filter cake had a constant weight, thereby obtaining a thermally conductive filler matrix;
[0073] Weigh 60 parts by weight of a thermally conductive filler matrix, 3 parts of silver nanowires, and 8 parts of single-walled carbon nanotubes and mix them evenly to obtain a thermally conductive filler;
[0074] Weigh out by weight: 100 parts of polyvinyl chloride, 30 parts of thermal conductive filler, 30 parts of phthalic acid diester, 3 parts of diester zinc stabilizer, 1 part of polyethylene wax, 0.5 parts of 2,6-di-tert-butyl-p-cresol and 1 part of UV-326, and mix them evenly to obtain composite polyvinyl chloride.
[0075] S2. Preparation of thermal insulation filler
[0076] Magnesium oxide particles, magnesium carbonate particles and hydrogen peroxide solution were added into a reactor in a dosage ratio of 5g:2g:8mL, and reacted at room temperature for 2h. After the reaction was completed, the filter cake was filtered and placed in a reactor at a temperature of 80°C to dry until the filter cake had a constant weight, thereby obtaining an activated filler matrix;
[0077] The activated filler matrix and 1 wt% 3-aminopropyltriethoxysilane solution were added to the reactor at a dosage ratio of 1 g: 4 mL, the reactor temperature was raised to 50° C., and the mixture was stirred for 1 h at a stirring rate of 160 rpm. After the reaction was completed, the filter cake was filtered and placed in a reactor at a temperature of 80° C. to dry until the filter cake had a constant weight, thereby obtaining a silanized filler matrix;
[0078] The silanized filler matrix is placed in a pressure of 10 -3 Torr ammonia nitriding furnace, introduce high-purity ammonia, maintain the gas pressure at 1 Torr, raise the temperature to 800°C, keep the temperature for 3 hours, gradually cool the sample chamber to room temperature, and obtain the modified filler matrix;
[0079] 30 parts of aluminum hydroxide particles, 40 parts of modified filler matrix, 10 parts of talcum powder, 5 parts of silicon micropowder and 10 parts of hollow glass beads were weighed and mixed evenly to obtain a thermal insulation filler.
[0080] S3. Preparation of polymer matrix
[0081] Benzoyl peroxide, toluene and dimethyl sulfoxide were added into the reaction kettle at a ratio of 1 g:12 mL:12 mL, and stirred at room temperature for 18 min at a stirring rate of 135 rpm to obtain an initiator solution;
[0082] The initiator solution, phenyl methacrylate, acrylonitrile and 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane were added into the reaction kettle at a ratio of 25 mL: 2 g: 5 g: 3 g: 4 g, the temperature of the reaction kettle was raised to 70° C., and the mixture was stirred for 3 h at a stirring rate of 150 rpm to obtain a polymer matrix solution;
[0083] The polymer matrix solution, the insulating filler and the deionized water were added into the reactor in the amount ratio of 80mL:25g:15mL, the temperature of the reactor was raised to 75°C, and the reaction was kept warm for 2h. The reaction liquid was placed on a rotary evaporator with the pressure set to 2-5kPa, and the solvent was removed by low-pressure evaporation until the precipitate reached a constant weight. The precipitate was placed in a drying oven at a temperature of 80°C until the precipitate reached a constant weight to obtain a composite polyolefin.
[0084] Weigh 40 parts of phthalic acid diester, 3 parts of calcium zinc heat stabilizer HX-10, 1 part of calcium stearate, 1 part of tert-butyl hydroxybenzoate and 0.5 part of UV-531 by weight, and mix them evenly to obtain an auxiliary material;
[0085] 100 parts of composite polyolefin and 25 parts of auxiliary materials are weighed and mixed evenly to obtain a composite cable material.
[0086] S4. Assemble the cables
[0087] A plurality of conductors 500 are arranged in parallel along their length direction to obtain a conductive core, wherein the conductor 500 is a copper core conductor with a surface coated with an insulating rubber layer;
[0088] The composite polyvinyl chloride is added into a twin-screw extruder, and the temperatures of the seven temperature sections of the twin-screw extruder from the feed port to the discharge port are 160°C, 165°C, 165°C, 170°C, 170°C, 180°C, and 180°C, respectively. The main engine speed of the twin-screw extruder is 100 rpm, and the pressure is 125 bar. After melt extrusion, the composite polyvinyl chloride is coated on the outside of the conductor 500 to obtain the insulating layer 200;
[0089] The shielding layer 300 is obtained by wrapping the insulating layer 200 with a copper tape;
[0090] The heat exchange layer 200 is obtained by winding a plurality of heat conducting pipes for conveying cooling liquid around the outside of the shielding layer, wherein the cooling pipes are made of aluminum alloy;
[0091] The composite cable material is added into a twin-screw extruder. The temperatures of the seven temperature zones of the twin-screw extruder from the feed port to the discharge port are 160°C, 165°C, 165°C, 170°C, 170°C, 180°C, and 180°C, respectively. The main engine speed of the twin-screw extruder is 100rpm, and the pressure is 125bar. After melt extrusion, it is coated on the outside of the heat exchange layer 200 to obtain a cable precursor. The cable precursor is transferred to a box filled with water vapor, kept warm for 7 hours, cooled and discharged to obtain a cable.
[0092] Example 3
[0093] S1. Preparation of composite polyvinyl chloride
[0094] Alumina particles and aluminum nitride particles were added into a calcining furnace at a mass ratio of 1:2, the furnace temperature was raised to 500°C, hexafluoropropylene gas was introduced at a rate of 0.3 L / min, and the reaction was carried out for 4 hours to obtain a fluorinated filler matrix;
[0095] A fluorinated filler matrix, a 2wt% 3-aminopropyltriethoxysilane solution and anhydrous ethanol were added to a reactor in a ratio of 10g:3g:40mL, the temperature of the reactor was raised to 120°C, and the reaction was kept warm for 3 hours. After the reaction was completed, the filter was filtered and the filter cake was placed in a drying oven at a temperature of 80°C and dried until the filter cake had a constant weight, thereby obtaining a thermally conductive filler matrix;
[0096] Weigh 60 parts by weight of a thermally conductive filler matrix, 5 parts of silver nanowires, and 10 parts of single-walled carbon nanotubes and mix them evenly to obtain a thermally conductive filler;
[0097] 100 parts of polyvinyl chloride, 50 parts of thermal conductive filler, 30 parts of phthalic acid diester, 2 parts of diester zinc stabilizer, 2 parts of polyethylene wax, 0.5 parts of 2,6-di-tert-butyl-p-cresol and 1 part of UV-326 were weighed by weight and mixed evenly to obtain composite polyvinyl chloride.
[0098] S2. Preparation of thermal insulation filler
[0099] Add magnesium oxide particles, magnesium carbonate particles and hydrogen peroxide solution into a reactor at a ratio of 5g:3g:8mL, react at room temperature for 2h, and after the reaction is completed, filter and place the filter cake in a reactor at 80°C to dry until the filter cake has a constant weight, to obtain an activated filler matrix;
[0100] The activated filler matrix and 2 wt% 3-aminopropyltriethoxysilane solution were added to the reactor at a ratio of 2g:5mL, the temperature of the reactor was raised to 60°C, and the mixture was stirred for 2 hours at a stirring rate of 180rpm. After the reaction was completed, the filter cake was filtered and placed in a reactor at a temperature of 80°C to dry until the filter cake had a constant weight, thereby obtaining a silanized filler matrix;
[0101] The silanized filler matrix is placed in a pressure of 10 -3 Torr ammonia nitriding furnace, introduce high-purity ammonia, maintain the gas pressure at 1 Torr, raise the temperature to 800°C, keep the temperature for 3 hours, gradually cool the sample chamber to room temperature, and obtain the modified filler matrix;
[0102] 30 parts of aluminum hydroxide particles, 50 parts of modified filler matrix, 5 parts of talcum powder, 5 parts of silicon micropowder and 20 parts of hollow glass beads were weighed and mixed evenly to obtain a thermal insulation filler.
[0103] S3. Preparation of polymer matrix
[0104] Benzoyl peroxide, toluene and dimethyl sulfoxide were added into the reaction kettle at a ratio of 0.8 g:15 mL:12 mL, and stirred at room temperature for 20 min at a stirring rate of 150 rpm to obtain an initiator solution;
[0105] The initiator solution, phenyl methacrylate, acrylonitrile and 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane were added into the reaction kettle at a ratio of 25 mL: 5 g: 4 g: 3 g, the temperature of the reaction kettle was raised to 80° C., and the mixture was stirred for 4 hours at a stirring rate of 180 rpm to obtain a polymer matrix solution;
[0106] The polymer matrix solution, the insulating filler and the deionized water are added into the reactor in the amount ratio of 100mL:20-25g:120mL, the temperature of the reactor is raised to 80°C, and the reaction is kept warm for 2h. The reaction liquid is placed on a rotary evaporator with the pressure set to 2-5kPa, and the solvent is removed by low-pressure evaporation until the precipitate is constant weight. The precipitate is placed in a drying oven at a temperature of 80°C until the precipitate is constant weight to obtain a composite polyolefin.
[0107] Weigh 50 parts of phthalic acid diester, 5 parts of calcium zinc heat stabilizer HX-10, 2 parts of calcium stearate, 1 part of tert-butyl hydroxybenzoate and 1 part of UV-531 by weight, and mix them evenly to obtain an auxiliary material;
[0108] 100 parts of composite polyolefin and 30 parts of auxiliary materials are weighed and mixed evenly to obtain a composite cable material.
[0109] S4. Assemble the cables
[0110] A plurality of conductors 500 are arranged in parallel along their length direction to obtain a conductive core, wherein the conductor 500 is a copper core conductor with a surface coated with an insulating rubber layer;
[0111] The composite polyvinyl chloride is added into a twin-screw extruder, and the temperatures of the seven temperature sections of the twin-screw extruder from the feed port to the discharge port are 160°C, 165°C, 165°C, 170°C, 170°C, 180°C, and 180°C, respectively. The main engine speed of the twin-screw extruder is 120rpm, and the pressure is 150bar. After melt extrusion, the composite polyvinyl chloride is coated on the outside of the conductor 500 to obtain the insulating layer 200;
[0112] The shielding layer 300 is obtained by wrapping the insulating layer 200 with a copper tape;
[0113] The heat exchange layer 200 is obtained by winding a plurality of heat conducting pipes for conveying cooling liquid around the outside of the shielding layer, wherein the cooling pipes are made of aluminum alloy;
[0114] The composite cable material is added into a twin-screw extruder. The temperatures of the seven temperature zones of the twin-screw extruder from the feed port to the discharge port are 160°C, 165°C, 165°C, 170°C, 170°C, 180°C, and 180°C, respectively. The main engine speed of the twin-screw extruder is 120rpm, and the pressure is 150bar. After melt extrusion, it is coated on the outside of the heat exchange layer 200 to obtain a cable precursor. The cable precursor is transferred to a box filled with water vapor, kept warm for 8 hours, cooled and discharged to obtain a cable.
[0115] Comparative Example 1
[0116] The difference between this comparative example and Example 3 is that step S2 is eliminated and an equal amount of aluminum hydroxide particles is used to replace the insulating filler in step S3.
[0117] Comparative Example 2
[0118] The difference between this comparative example and Example 3 is that step S3 is changed and an equal amount of polyvinyl chloride is used to replace the polymer matrix in step S3.
[0119] Comparative Example 3
[0120] The difference between this comparative example and Example 3 is that step S3 is eliminated and an equal amount of polyvinyl chloride is used to replace the composite cable material in step S4.
[0121] Comparative Example 4
[0122] The difference between this comparative example and Example 3 is that step S1 is eliminated and an equal amount of polyvinyl chloride is used to replace the composite polyvinyl chloride in step S4.
[0123] Performance Test:
[0124] The wear resistance, thermal insulation performance, flame retardant performance, high temperature resistance and mechanical strength of the cables prepared in Examples 1-3 and Comparative Examples 1-3 were tested; the wear resistance of the cable was measured according to the standard GB / T 17737.324-2018 "Coaxial Communication Cable Part 1-324: Mechanical Test Method Cable Abrasion Resistance Test"; the thermal insulation performance of the cable was measured according to the standard JB / T 10181.21-2014 "Cable Current Carrying Capacity Calculation Part 21: Calculation of Thermal Resistance"; the mechanical strength of the cable material was measured according to the standard GB / T 17737.316-2018 "Coaxial Communication Cable Part 1-316: Mechanical Test Method Cable Maximum Tensile Test" to determine the maximum load of the sample; the flame retardant performance was measured according to the standard GB / T 19666-2019 "General Rules for Flame Retardant and Fire Resistant Wires, Cables or Optical Cables" determines the flame retardant grade of the cable; the high temperature resistance performance refers to the standard GB / T2951.42-2008 "General Test Methods for Insulation and Sheathing Materials of Electric and Optical Cables Part 42: Special Test Methods for Polyethylene and Polypropylene Mixtures Tests for Tensile Strength and Elongation at Break after High Temperature Treatment Winding Test after High Temperature Treatment Winding Test after Air Heat Ageing Determination of Mass Increase Long-term Thermal Stability Test Copper Catalyzed Oxidative Degradation Test Method Determination of Cable" Determine the softness of the cable after high temperature treatment and the cracking of the cable after insulation at 100℃ for 42 days; see Table 1 for specific test data:
[0125] Table 1. Performance test data of samples
[0126]
[0127] The thermal conductivity, wear resistance and mechanical properties of the insulating layers prepared in Examples 1-3 and Comparative Example 4 were tested. The thermal conductivity was measured according to the standard JB / T 10181.21-2014 "Cable Current Carrying Capacity Calculation Part 21: Calculation of Thermal Resistance", and the mechanical strength was measured according to the standard GB / T17737.316-2018 "Coaxial Communication Cable Part 1-316: Mechanical Test Method Cable Maximum Tensile Test" to determine the maximum load of the insulating layer; the wear resistance was measured according to the standard GB / T 17737.324-2018 "Coaxial Communication Cable Part 1-324: Mechanical Test Method Cable Abrasion Resistance Test", and the specific test data are shown in Table 2:
[0128] Table 2. Performance test data of insulation layer
[0129]
[0130]
[0131] Data Analysis:
[0132] A comparative analysis of the data in Table 1 shows that the thermal resistance coefficient of the wear-resistant liquid-cooled cable with ultra-large current load for new energy prepared by the present invention reaches 8.58K·m / W, the number of blade scraping cycles reaches 73 times, the maximum load reaches 188N, the bundled combustion level reaches V-0, the number of winding turns of the cable after high temperature treatment reaches 6 turns, and the cable does not crack after being treated at 100°C for 42 days; by comparing the data of Example 3 and Comparative Example 1, Comparative Example 2 and Comparative Example 3, it can be found that the composite polyolefin obtained by preparing a thermal insulation filler and a polymer matrix and closely combining them through silanization can significantly improve the performance of the cable, so that it meets the requirements of thermal insulation, wear resistance, high temperature resistance and high mechanical strength, thereby obtaining a high-performance wear-resistant liquid-cooled cable.
[0133] A comparative analysis of the data in Table 2 shows that the thermal resistance coefficient of the insulation layer prepared by the present invention is only 1.08 K·m / W, the number of blade scraping cycles reaches 54, and the maximum load is 151 N. By comparing the data of Example 3 and Comparative Example 1, it can be found that after fluorination and silanization, the thermal conductive filler prepared by the present invention can not only improve the insulation capacity of the insulation layer but also make it closely combined with other inorganic materials, thereby obtaining an insulation layer with wear resistance, heat conductivity, high mechanical strength and strong insulation performance, and then obtaining a cable with ultra-high current load.
[0134] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0135] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0136] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A wear-resistant liquid-cooled cable with ultra-large current load for new energy, characterized in that: The invention comprises a plurality of conductors (500), wherein an insulating layer (400), a shielding layer (300) and an outer sheath layer (100) are sequentially arranged outside the plurality of conductors (500); a heat exchange layer (200) composed of a plurality of heat exchange tubes is arranged between the shielding layer (300) and the outer sheath layer (100), and the plurality of heat exchange tubes are all arranged in a spiral shape; The insulating layer (400) is obtained by extruding composite polyvinyl chloride and coating it on the outside of the conductor (500); The shielding layer (300) is obtained by coating the insulating layer (400) with a copper tape; The heat exchange layer (200) is obtained by winding a plurality of heat-conducting pipes for conveying cooling liquid around the outside of the shielding layer, wherein the cooling pipes are made of aluminum alloy; The outer sheath layer (100) is obtained by extruding a composite cable material and coating it on the outside of the heat exchange layer (200); The composite cable material comprises the following components by weight: 100 parts of composite polyolefin and 20-30 parts of auxiliary materials, wherein the polymer is a mixture of a polymer matrix and a heat insulating filler; The preparation method of the thermal insulation filler comprises the following steps: B1. Add magnesium oxide particles, magnesium carbonate particles and hydrogen peroxide solution into a reactor, react at room temperature for 1-2 hours, and post-treat to obtain an activated filler matrix, wherein the amount ratio of magnesium oxide particles, magnesium carbonate particles and hydrogen peroxide solution is 3-5g:2-3g:5-8mL; B2, adding the activated filler matrix and 0.5-2wt% 3-aminopropyltriethoxysilane solution into a reaction kettle, raising the temperature of the reaction kettle to 40-60° C., keeping warm and stirring for 1-2 hours, and post-treating to obtain a silanized filler matrix; B3, placing the silanized filler matrix into an ammonia nitriding furnace with a pressure of 10-2-10-3Torr, introducing high-purity ammonia, maintaining the pressure at 0.1-1Torr, raising the temperature to 500-800°C, keeping the temperature for reaction for 2-3 hours, and gradually cooling the sample chamber to room temperature to obtain a modified filler matrix; B4, weigh 30 parts of aluminum hydroxide particles, 30-50 parts of modified filler matrix, 5-10 parts of talc, 5-10 parts of silica powder and 5-20 parts of hollow glass beads by weight and mix them evenly to obtain an insulating filler; The preparation method of the composite polyolefin comprises the following steps: C1. Add benzoyl peroxide, toluene and dimethyl sulfoxide into a reaction kettle and stir at room temperature for 15-20 minutes to obtain an initiator solution; C2, adding the initiator solution, phenyl methacrylate, acrylonitrile and 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane into the reaction kettle, raising the temperature of the reaction kettle to 60-80° C., and stirring for 2-4 hours to obtain a polymer matrix solution; C3. Add the polymer matrix solution, thermal insulation filler and deionized water into the reactor, increase the temperature of the reactor to 70-80°C, keep the temperature for 1-2 hours, and perform post-treatment to obtain the composite polyolefin.
2. A wear-resistant liquid-cooled cable with ultra-large current load for new energy according to claim 1, characterized in that: The composite polyvinyl chloride comprises the following components in parts by weight: 100 parts of polyvinyl chloride, 20-50 parts of thermal conductive fillers, 30-50 parts of plasticizers, 2-5 parts of stabilizers, 0.5-2 parts of lubricants, 0.5-1 parts of antioxidants and 0.5-1 parts of ultraviolet stabilizers, the plasticizer is a diester of phthalic acid, the stabilizer is one or more of a diester zinc stabilizer, a calcium zinc heat stabilizer HX-10 and a lead-free calcium zinc stabilizer LX-800, the lubricant is one or more of hard magnesium stearate, calcium stearate, zinc stearate and polyethylene wax, the antioxidant is one or more of 2,6-di-tert-butyl-p-cresol, triphosphate and di-tert-butyl-p-phenol, and the ultraviolet stabilizer is one or more of UV-326, UV-327 and HALS.
3. A wear-resistant liquid-cooled cable with ultra-large current load for new energy according to claim 2, characterized in that: The preparation method of the thermal conductive filler comprises the following steps: A1. Add alumina particles and aluminum nitride particles into a calcining furnace, raise the furnace temperature to 400-600°C, introduce hexafluoropropylene gas at a rate of 0.1-0.5 L / min, and keep the temperature for 2-4 hours to obtain a fluorinated filler matrix; A2, adding the fluorinated filler matrix, 0.5-2wt% 3-aminopropyltriethoxysilane solution and anhydrous ethanol into a reaction kettle, raising the temperature of the reaction kettle to 80-120° C., keeping the temperature for 1-3 hours, and post-treating to obtain a thermally conductive filler matrix; A3. Weigh 60 parts of thermal conductive filler matrix, 2-5 parts of silver nanowires and 5-10 parts of single-walled carbon nanotubes by weight and mix them evenly to obtain a thermal conductive filler.
4. A wear-resistant liquid-cooled cable with ultra-large current load for new energy according to claim 3, characterized in that: In step A1, the weight ratio of aluminum oxide particles to aluminum nitride particles is 1-2:2-4; in step A2, the amount ratio of the fluorinated filler matrix, 0.5-2wt% 3-aminopropyltriethoxysilane solution and anhydrous ethanol is 8-10g:2-3g:40-50mL, and the post-treatment includes: after the reaction is completed, filtering, placing the filter cake in a drying oven at a temperature of 80°C and drying it until the filter cake has a constant weight, to obtain a thermally conductive filler matrix.
5. The wear-resistant liquid-cooled cable with ultra-large current load for new energy according to claim 1, characterized in that: In step B1, the post-treatment includes: after the reaction is completed, filtering with suction, placing the filter cake in a reactor at a temperature of 80°C and drying it until the filter cake has a constant weight, thereby obtaining an activated filler matrix; in step B2, the amount ratio of the activated filler matrix to the 0.5-2wt% 3-aminopropyltriethoxysilane solution is 1-2g:4-5mL, and the stirring rate is 120-180rpm. The post-treatment includes: after the reaction is completed, filtering with suction, placing the filter cake in a reactor at a temperature of 80°C and drying it until the filter cake has a constant weight, thereby obtaining a silanized filler matrix.
6. The wear-resistant liquid-cooled cable with ultra-large current load for new energy according to claim 1, characterized in that: In step C1, the amount ratio of benzoyl peroxide, toluene and dimethyl sulfoxide is 0.8-1g:12-15mL:12-15mL, and the stirring rate is 120-150rpm; in step C2, the amount ratio of initiator solution, phenyl methacrylate, acrylonitrile and 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane is 25-30mL:3-5g:3-4g:3-4g, and the stirring rate is 120-180rpm; in step C3, the amount ratio of polymer matrix solution and thermal insulation filler is 80-100mL:20-25g, and the post-treatment operation is: placing the reaction solution on a rotary evaporator, setting the pressure to 2-5kPa, low-pressure evaporation to remove the solvent until the precipitate is constant weight, placing the precipitate in a drying oven at a temperature of 80°C until the precipitate is constant weight, and obtaining a composite polyolefin.
7. The wear-resistant liquid-cooled cable with ultra-large current load for new energy according to claim 1, characterized in that: Insulation layer (400) extrusion coating The method comprises the following steps: adding composite polyvinyl chloride into a twin-screw extruder, wherein the temperatures of seven temperature sections of the twin-screw extruder from the feed port toward the discharge port are 160°C, 165°C, 165°C, 170°C, 170°C, 180°C, and 180°C in sequence, the main engine speed of the twin-screw extruder is 80-120rpm, the pressure is 100-150bar, and after melt extrusion, the composite polyvinyl chloride is coated on the outside of the conductor (500) to obtain an insulating layer (400).
8. The wear-resistant liquid-cooled cable with ultra-large current load for new energy according to claim 1, characterized in that: The extrusion coating of the outer sheath layer (100) comprises the following steps: adding the composite cable material into a twin-screw extruder, wherein the temperatures of the seven temperature sections of the twin-screw extruder from the feed port to the discharge port are 160°C, 165°C, 165°C, 170°C, 170°C, 180°C, and 180°C respectively, the main engine speed of the twin-screw extruder is 80-120rpm, and the pressure is 100-150bar; after melt extrusion, the material is coated on the outside of the shielding layer (200) to obtain a cable precursor; the cable precursor is transferred to a box filled with water vapor, subjected to heat preservation treatment for 6-8h, cooled and discharged to obtain a cable.
Citation Information
Patent Citations
Intelligent fireproof medium-voltage cable and preparation method thereof
CN111477401A
Large-section flame-delay-resistant mobile wear-resistant and drag-resistant shielding cable
CN116631675A
Temperature-resistant copper conductor cable for computer and preparation method thereof
CN117133506A
Cited By
New energy liquid cooling cable charging assembly and processing method thereof
CN121122830A